A Validated UV-Spectrophotometric Method for the Estimation of Ofloxacin in Bulk and Pharmaceutical Dosage Form - Dash, Arun Kumar (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT: A new, simple, precise and accurate method for the estimation of Ofloxacin in bulk and pharmaceutical dosage forms has been developed. 0.1N HCl was chosen as the solvent system. The Î»max was found to be 293nm. The responses were linear in the range of 02-20Âµg/ml. The regression equation of the calibration graph and correlation coefficient were found to be y = 0.121x - 0.015 and 0.999 respectively. Validation of the method was done in order to demonstrate accuracy, precision, interday and intraday assay, robustness, and ruggedness, of the proposed method. The %RSD values for both intraday and interday precision were less than 1%. The recovery of the drug from the sample was ranged between 97.792% and 100.49%. Commercial tablets containing 200mg of Ofloxacin (Oflxcin and Acoflox) were analyzed by the proposed method and the results were well within the claimed limits.